Lockdown e “Chiesa in uscita”. Un caso di studio in Italia: la fraternità “AGBP” - Turco, Daniela (Comparative Cultural Studies: European and Latin American Perspectives, 2021)
The impetuosity of the Sars-Covid 2 infection has been remarkable, quickly upsetting the habits of individuals in every seat of the planet. We can observe, on the one hand, the individuals, lost and called to redefine every area of their daily lives. On the other, the institutions that, seizing this loss, have been called to play their essential role of creating and strengthening social bonds. The Catholic Church has promoted respect for the norms, without renouncing a “religious offer” which seems to have responded to an effective demand for accompaniment with a lot of possibility to chose on line liturgical celebrations, with a multiplicity of forms and possibilities of access. Among the various options possible, it was decided to focus attention on a specific case: the case of the fraternity “Amici di Gesù Buon Pastore” (AGBP), which has experienced a significant increase in its followers in the days of lockdown. In particular, we will ask ourselves what so many spiritual-followers have been looking for and if (and how) this interest, born during the quarantine period, can transform the new forms of religious belonging into a context where the historical religions seem to be unattractive if compared to the many alternatives of spirituality present on the “market”.